Continuous Gas‐Phase Hydroaminomethylation using Supported Ionic Liquid Phase Catalysts1. Issue 27 (16th May 2013) - Schneider, Martin Johannes; Lijewski, Martin; Woelfel, René; Haumann, Marco; Wasserscheid, Peter
<x xml:space="preserve">Abstract</x> Just SILP‐ing through: Hydroaminomethylation of ethylene and diethylamine to diethylpropylamine is demonstrated as a continuous gas‐phase reaction (see picture) using a supported ionic liquid phase (SILP) to immobilize the applied homogenous Rh‐Xantphos catalyst. Highly selective and long‐term stable (18 days) catalyst operation was obtained if the ionic liquid was of low basicity and lipophilicity combined with a porous activated carbon support.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>